2015
DOI: 10.1152/ajprenal.00593.2013
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of transient receptor potential M6 channels as a cause of hypermagnesiuric hypomagnesemia in obese type 2 diabetic rats

Abstract: We assessed the expression profile of Mg(2+)-transporting molecules in obese diabetic rats as a cause of hypermagnesiuric hypomagnesemia, which is involved in the development of insulin resistance, hypertension, and coronary diseases. Kidneys were obtained from male Otsuka Long-Evans Tokushima fatty (OLETF) and Long-Evans Tokushima Otsuka (LETO) obese diabetic rats at the ages of 16, 24, and 34 wk. Expression profiles were studied by real-time PCR and immunohistochemistry together with measurements of urine Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 62 publications
(70 reference statements)
2
20
0
Order By: Relevance
“…Moreover, in kidneys of the LowMg-HFD mice, a lower mRNA expression of other DCT-specific genes, such as Slc12a3, Pvalb, and Klk1, was observed (24). These findings are in line with a study that observed reduced renal Trpm6 and Slc12a3 mRNA and protein levels in diabetic (Otsuka Long-Evans Tokushima fatty) rats (27). It is, however, not clear from this study if the reduced Trpm6 levels are a direct consequence of the lower Slc12a3 expression or if the DCT itself is affected.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, in kidneys of the LowMg-HFD mice, a lower mRNA expression of other DCT-specific genes, such as Slc12a3, Pvalb, and Klk1, was observed (24). These findings are in line with a study that observed reduced renal Trpm6 and Slc12a3 mRNA and protein levels in diabetic (Otsuka Long-Evans Tokushima fatty) rats (27). It is, however, not clear from this study if the reduced Trpm6 levels are a direct consequence of the lower Slc12a3 expression or if the DCT itself is affected.…”
Section: Discussionsupporting
confidence: 88%
“…The mRNA expression of TRPM6 is changed in diabetic rats, although results are contradictory and may depend on the experimental model used (96,97). Whereas some report increased TRPM6 expression (96), others show that TRPM6 is downregulated (97). Given that hypomagnesemia itself also stimulates TRPM6 expression (77,98), it is difficult to distinguish between the effect of hypomagnesemia and T2DM in these studies.…”
Section: Trpm6mentioning
confidence: 95%
“…However, these differences may be explained by the dietary Mg 2+ intake of the subjects, since patients in the original study showed reduced Mg 2+ intake (,250 mg/day) (71). The mRNA expression of TRPM6 is changed in diabetic rats, although results are contradictory and may depend on the experimental model used (96,97). Whereas some report increased TRPM6 expression (96), others show that TRPM6 is downregulated (97).…”
Section: Trpm6mentioning
confidence: 99%
“…Magnesiuria is likely caused by the reduced activity of the transient receptor potential melastatin 6 (TRPM6) ion channel in the distal convoluted tubules and is possibly related to insulin resistance . In fact, a downregulation of TRPM6 channels, hypermagnesiuria, and hypomagnesemia were observed in obese T2D rats . Hence, the improvement of insulin resistance observed after SGLT2i administration may be associated with reduced magnesium excretion through TRPM6.…”
Section: Clinical and Preclinical Studies On Electrolytes Imbalancesmentioning
confidence: 99%